Taxonomic redefinition of Bupleurum pauciradiatum and B. wolffianum (Apiaceae) - Stoyanov, Stoyan (Phytotaxa, 2018)
Bupleurum pauciradiatum is recorded for the first time in the Balkans. It was discovered in the Kaliakra Reserve, the Bulgarian North Black Sea coast. A revised species description and comparison with its morphologically closest taxa—B. asperuloides and B. wolffianum—are given. The name B. pauciradiatum was misused in the countries of Transcaucasia for B. wolffianum. Bupleurum wolffianum is found conspecific with B. leptocladum, and the latter is reduced into synonymy. The records of B. pauciradiatum in the Crimea belong to B. asperuloides.